Strategi Edukasi Sejarah Lokal Melalui Animasi Interaktif Museum Fatahillah Sebagai Upaya Meningkatkan Minat Generasi Muda - Nicole Wijaya (VisArt: Jurnal Seni Rupa dan Design, 2025)
The Fatahillah Museum, located in Kota Tua, Jakarta, is a historical landmark that was originally built as the town hall during the era of the Dutch East India Company (VOC). Today, it serves as a museum that preserves and displays important historical artifacts from Batavia’s colonial past. Despite its rich cultural and historical value, the museum faces low engagement from the younger generation, who often perceive historical sites as outdated or irrelevant. This study aims to explore effective ways to increase youth interest and appreciation for the Fatahillah Museum and its historical significance. To achieve this, the study utilizes a qualitative research method, including direct observation, in depth interviews, and literature review. Findings indicate that the use of animation featuring engaging visual styles, narrative storytelling, and accessible language can significantly enhance the delivery of historical content. The combination of educational messages and creative visuals helps bridge the gap between traditional history and contemporary youth culture. In conclusion, animation proves to be a promising medium to make learning about cultural heritage more appealing, interactive, and relatable to the younger generation